Morphological study of remineralization of the eroded enamel lesions by tyrosine-rich amelogenin peptide - Mingzhu Wen; Qinghua Bai; Yiwei Li; Yaru Li; Dandan Ma; Jinpu Chu (BMC, 2024)
Abstract Background Tyrosine-rich amelogenin peptide (TRAP) is the main amelogenin digestion product in the developmental enamel matrix. It has been shown to promote remineralization of demineralized enamel in our previous study. However, direct evidence of the effect of TRAP on the morphology and nanostructure of crystal growth on an enamel surface has not been reported. This study aimed to examine the effect of TRAP on the morphology of calcium phosphate crystals grown on early enamel erosion using a pH-cycling model. Methods Eroded lesions were produced in human premolars by 30-second immersion in 37% phosphoric acid. Forty-five samples of eroded human premolar enamel blocks were selected and randomly divided into 3 groups: deionized water (DDW, negative control); 100 µg/mL TRAP, and 2 ppm sodium fluoride (NaF, positive control group). For 14 days, the specimens were exposed to a pH-cycling model. Using scanning electron microscopy (SEM) and atomic force microscopy (AFM) methods, the surface morphology, calcium-phosphorus ratio, and enamel surface roughness were examined. X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR) were used to assess crystal characteristics. Results After pH-cycling, compared to the two control groups, the surface of the eroded enamel of the peptide TRAP group shows a large number of new, densely arranged rod-like crystals, parallel to each other, regularly arranged, forming an ordered structure, with crystal morphology similar to that of natural enamel. The crystals are mostly hydroxyapatite (HA). Conclusion This study demonstrates that the peptide TRAP modulates the formation of hydroxyapatite in eroded enamel and that the newly formed crystals resemble natural enamel crystals and promote the remineralization of enamel, providing a promising biomaterial for remineralization treatment of enamel lesions.